From Perceived Supervisor Social Power to Employee Commitment: Definition and Scale Development - Chénard-Poirier, Léandre Alexis; Vandenberghe, Christian; Morin, Alexandre J. S. (Frontiers in Psychology, 2021)
It has been theoretically proposed that employees’ perceptions of their supervisor social power in the organization entail a potential to influence their beliefs, attitudes, and behaviors. However, no study has investigated such potential. This lack of research stems from the absence of a common understanding around the meaning of perceived supervisor social power (PSSP) and the absence of any validated measure. Therefore, the purpose of this article is to establish PSSP definition and to validate a five-item scale to measure this construct. Three studies encompassing four independent samples of employees from three different countries and three different languages (i.e., France, cross-sectional [Study 1, Sample 1], Canada, cross-sectional [Study 1, Sample 2: French Canada; Study 2: English Canada], Romania, two-wave data collection [Study 3]) were conducted to assess the validity of PSSP. Results showed that responses to the PSSP scale presented excellent psychometric properties (i.e., factor validity, reliability, and convergent and discriminant validity). Furthermore, the structure of the proposed five-item measure of PSSP was found to be invariant across four samples. Finally, PSSP nomological validity (i.e., integration into a nomological network) was assessed. Study 1 and Study 2 showed that PSSP was positively related to affective organizational commitment. All three studies showed that PSSP acted as a positive moderator of the relation between affective commitment to the supervisor and affective organizational commitment. Together, these studies support the psychometric soundness of the PSSP scale and presented the first evidence of its potential to influence followers. Implications of these findings for future research on supervisor social power are discussed.